2018
DOI: 10.1364/oe.26.00a562
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for direct crown base height estimation of individual conifer trees using airborne LiDAR data

Abstract: Abstract:Crown base height (CBH) is an essential tree biophysical parameter for many applications in forest management, forest fuel treatment, wildfire modeling, ecosystem modeling and global climate change studies. Accurate and automatic estimation of CBH for individual trees is still a challenging task. Airborne light detection and ranging (LiDAR) provides reliable and promising data for estimating CBH. Various methods have been developed to calculate CBH indirectly using regression-based means from airborne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…Accurate individual tree height extraction is the key to AGB estimation for individual trees. As the literature [19,44] shows, the R 2 of extracted tree heights from airborne LiDAR-acquired point cloud data is by far higher than 0.90. Even in some dense seasonal tropical forests, the R 2 is still as high as 0.94 [28].…”
Section: Discussionmentioning
confidence: 94%
“…Accurate individual tree height extraction is the key to AGB estimation for individual trees. As the literature [19,44] shows, the R 2 of extracted tree heights from airborne LiDAR-acquired point cloud data is by far higher than 0.90. Even in some dense seasonal tropical forests, the R 2 is still as high as 0.94 [28].…”
Section: Discussionmentioning
confidence: 94%
“…Remote sensing has the potential to provide consistent, reproducible and up-to-date information on various forest parameters in order to make inventories more efficient [6]. Previous studies mostly applied a specific remote sensing system to a single area and demonstrated how remote sensing can be used for quick assessment of forests at large spatial scales (see, e.g., [7][8][9][10][11][12][13][14][15][16]). Nevertheless, comparing novel remote sensing methods for measuring tree height usually involves a high degree of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…We achieved detection rates from 0.75 to 0.90, which is in line with other studies. For instance, Luo et al [35] reported overall accuracy of 0.87 for comparison between automatically segmented trees and visual examination in Tahoe National Forest (USA). Wang et al [7] reported R 2 of 0.8-0.9 for comparison of plot-level field-based and ALS-based tree counts in Heihe River Basin (China).…”
Section: Tree Detectionmentioning
confidence: 99%